Microstructure and mechanical properties of Al-7075 alloy processed by equal channel angular pressing combined with aging treatment - Shaeri, M.H.; Salehi, M.T.; Seyyedein, S.H.; Abutalebi, M.R.; Park, J.K. (Materials in engineering, 2014)
•Specimens were aged before ECAP, after ECAP and during ECAP at 393K and 423K.•Maximum mechanical properties achieved when microstructure mainly consists of fine η′ phase.•Dynamic aging during ECAP at 393K is the optimum process to gain maximum mechanical properties.•ECAP does not change the expected precipitation sequence but it accelerates the precipitation rate.•Ultrafine-grained materials with grain size less than 500nm obtained after final ECAP pass. In order to examine the combined effect of plastic deformation and aging process, the Al 7075 alloy was subjected to equal channel angular pressing (ECAP) deformation by route BC in various ECAP and aging conditions: pre-ECAP aging, post-ECAP aging and dynamic aging during ECAP at 393K and 423K. Followed by ECAP and aging treatment, Vickers microhardness and tensile test were performed and microstructural observations were undertaken using transmission electron microscopy (TEM) and X-ray diffractometer (XRD). TEM investigation showed that ultrafine-grained (UFG) materials with grain size less than 500nm could be obtained after three or four passes of ECAP. Precipitates characterization revealed that maximum mechanical properties are achieved when the microstructure mainly consists of fine dispersion of small η′ precipitates and minor quantities of GP zones. Dynamic aged specimens at 393K and 423K represented maximum and minimum mechanical properties, respectively, due to formation of fine η′ precipitates plus GP zones and η′ plus η precipitates, respectively. Dynamic aging during ECAP at 393K appeared preferable to other procedures for attaining maximum mechanical properties as well as saving time and energy.